Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1111/j.1600-0749.1993.tb00611.x
|View full text |Cite
|
Sign up to set email alerts
|

From the Crest to the Periphery: Control of Pigment Cell Migration and Lineage Segregation

Abstract: Pigment cells are one of many cell types derived from the neural crest. This review focuses on the mechanisms that control the timing and pathways of migration of pigment cells into the epidermis and determinants that control the differentiation of pigment cells. Several factors may control the timing and pattern of pigment cell migration in the dorsolateral space including the loss of inhibitory molecules in the pathway, the appearance of chemotactic molecules emanating from the dispersing dermatome, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0
5

Year Published

1994
1994
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 114 publications
(85 reference statements)
1
49
0
5
Order By: Relevance
“…Signaling through the KIT receptor is critical for the growth, survival, and migration of melanocyte precursors (reviewed by Erickson 1993). It has been shown that both phospholipase C activation and Ca 21 influx are important in supporting KIT-positive cells (Berger 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Signaling through the KIT receptor is critical for the growth, survival, and migration of melanocyte precursors (reviewed by Erickson 1993). It has been shown that both phospholipase C activation and Ca 21 influx are important in supporting KIT-positive cells (Berger 2006).…”
Section: Resultsmentioning
confidence: 99%
“…In early development, the path taken by pigment cells is likely to be controlled either by a chemotactic mechanism (13)(14)(15)(16)(17) or by guidance cues in the extracellular matrix (18). We postulate that the iridophore cells move chemotactically in response to one of the morphogens, and that the flux of these cells relative to the melanophore cells comprises both a diffusional component caused by random motion and a directed component that results from the tactic response.…”
mentioning
confidence: 99%
“…the inner ear (reviewed in Erickson, 1993). EmbryologMelanocytes are found distributed in several organs, ically, melanocytes share with sensory and sympathetic such as the epidermis, the leptomeninges, the eye, and neurons a neural crest progenitor (reviewed in Holbrook et al, 1988).…”
Section: Introductionmentioning
confidence: 99%